STUDY AND HYGIENIC EVALUATION OF INDIVIDUAL DIETARY PATTERNS OF STUDENTS OF TASHKENT STATE MEDICAL UNIVERSITY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The present study provides a hygienic assessment of the individual dietary patterns of 156 students enrolled at Tashkent State Medical University. The analysis included daily food intake, energy expenditure, and the consumption levels of proteins, fats, and carbohydrates compared with established nutritional standards. Seasonal factors were considered when evaluating meal frequency and distribution throughout the day. The findings revealed that the intake of several food groups does not comply with recommended physiological requirements.
Keywords: balanced diet, healthy lifestyle, meal pattern, breakfast, lunch, dinner, nutrients, physiological standards.